2020
DOI: 10.2196/20548
|View full text |Cite
|
Sign up to set email alerts
|

New York Inner City Hospital COVID-19 Experience and Current Data: Retrospective Analysis at the Epicenter of the American Coronavirus Outbreak

Abstract: Background In the midst of the coronavirus disease pandemic, emerging clinical data across the world has equipped frontline health care workers, policy makers, and researchers to better understand and combat the illness. Objective The aim of this study is to report the correlation of clinical and laboratory parameters with patients requiring mechanical ventilation and the mortality in patients infected with severe acute respiratory syndrome coronavirus … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 5 publications
4
19
0
1
Order By: Relevance
“…Abnormalities in markers of cellular injury, particularly elevated lactate dehydrogenase (LDH), have been linked to greater disease severity. 6,9,10,20,75,81,103 Recent data suggest that LDH may be related to respiratory function and be an important predictor of respiratory failure in COVID-19 patients. 104 A prediction model using age, LDH, and CD4+ ([age × LDH]/CD4) showed that the area under the receiver operating characteristic (ROC) curve was significantly higher than the areas for each of these variables alone.…”
Section: Non-specific Biomarkers Of Cellular Injurymentioning
confidence: 99%
“…Abnormalities in markers of cellular injury, particularly elevated lactate dehydrogenase (LDH), have been linked to greater disease severity. 6,9,10,20,75,81,103 Recent data suggest that LDH may be related to respiratory function and be an important predictor of respiratory failure in COVID-19 patients. 104 A prediction model using age, LDH, and CD4+ ([age × LDH]/CD4) showed that the area under the receiver operating characteristic (ROC) curve was significantly higher than the areas for each of these variables alone.…”
Section: Non-specific Biomarkers Of Cellular Injurymentioning
confidence: 99%
“…Although global epidemiological data suggest a similar prevalence in virus infection between men and women, a clear sex-related difference in the severity of the disease, with a more favorable outcome in women compared to men, has been described [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Indeed, according to the last update of the global situation on October 14, 2020 the overall prevalence of infection in men and women was 53.3 and 46.7%, respectively, whereas the prevalence of death in men and women was 58.3 and 41.7%, respectively.…”
Section: Sex Disparities In the Severity And Outcome Of Covid-19mentioning
confidence: 99%
“…After screening, 27 articles were included for further analysis. 20 46 The process of selection of the included studies is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 22,578 patients with COVID-19 infection in 15 of the included studies, [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] a total of 6315 patients died during the study period: 725 patients in the CKD group and 5590 patients in the non-CKD group. The heterogeneity test showed moderate heterogeneity among these studies (I 2 = 43%), and a random-effects model was used for this meta-analysis.…”
Section: All-cause Mortalitymentioning
confidence: 99%